Effect of tolerance factor and A-site cations disorderon transport properties of A’₁₋ₓA’’ₓCoO₃₋δ perovskites (A’ = Ho, Er; A’’ = Ca, Sr) - Kozlovskii, A.A.; Khirnyi, V.F.; Semenov, A.V.; Puzikov, V.M.; Deineka, T.G.; Gaiduk, O.V.; Chiang, Yu.N. (Functional Materials, 2009)
Temperature dependences of conductivity for Ho₁₋ₓSrₓCoO₃₋δ, Er₁₋ₓSrₓCoO₃₋δ, Ho₁₋ₓCaₓCoO₃₋δ and Er₁₋ₓCaₓCoO₃₋δ (x ~ 0.15, 0.25, 0.35, 0.45, 0.55, 0.65, 0.75, 0.85, 0.95) having the ABO₃ perovskite structure have been studied in the T>77 K temperature region. All the compounds studied are characterized by hopping conduction with the temperature dependence of conductivity ρ(T) = ρ∞exp(T0/T)₁/n. Depending on the distribution dispersion σ² of A cationic radii, different types of the hopping conduction are realized. In most samples, the conduction occurs as the variable range hopping conduction in the Mott mode (n = 4). In the Ho₁₋ₓSrₓCoO₃₋δ system, a transition to the hopping conduction over the nearest sites occurs as the σ² increases (n = 1); while in the Er₁₋ₓSrₓCoO₃₋δ, to the Efros-Shklovsky mode (n = 2). In Ho₁₋ₓSrₓCoO₃₋δ samples, the spin conduction channel arises as the temperature rises up to 190-270 K due to cobalt ion transition into excited state. В області температур Т> 77 К досліджено температурні залежності питомого електричного опору керамік Ho₁₋ₓSrₓCoO₃₋δ, Er₁₋ₓSrₓCoO₃₋δ, Ho₁₋ₓCaₓCoO₃₋δ та Er₁₋ₓCaₓCoO₃₋δ (х = 0,15; 0,25; 0,35; 0,45; 0,55; 0,65; 0,75; 0,85; 0,95), що мають структуру перовскіту АВО₃. Вивчені сполуки характеризуються стрибковою провідністю з температурною залежністю електроопору ρ(Т) = ρ∞ехр(Т0/Т)₁/n. Залежно від дисперсії розподілу σ² радіусів А-катіонів реалізуються різні типи стрибкової провідності. У більшості зразків провідність здійснюється за механізмом стрибкової провідності зі змінною довжиною стрибка у режимі Мотта (n = 4). У системі Ho₁₋ₓSrₓCoO₃₋δ при збільшенні величини σ² відбувається перехід до стрибкової провідності поміж найближчими сусідами (n = 1 ); а у системі Er₁₋ₓSrₓCoO₃₋δ - до режиму Ефроса-Шкловського (n = 2). У зразках Ho₁₋ₓSrₓCoO₃₋δ при підвищенні температури до 190-270 К виявлено появу спінового каналу провідності, пов'язану з переходом іонів кобальту у збуджений стан. В области температур Т>77 К исследованы температурные зависимости удельного электрического сопротивления р керамик Ho₁₋ₓSrₓCoO₃₋δ, Er₁₋ₓSrₓCoO₃₋δ, Ho₁₋ₓCaₓCoO₃₋δ и Er₁₋ₓCaₓCoO₃₋δ (х = 0,15; 0,25; 0,35; 0,45; 0,55; 0,65; 0,75; 0,85; 0,95), обладающих структурой перовскита АВО₃. Изученные соединения характеризуются прыжковой проводимостью с температурной зависимостью электросопротивления ρ(Т) = ρ∞ехр(Т0/Т)₁/n. В зависимости от дисперсии распределения σ² радиусов А-катионов реализуются различные типы прыжковой проводимости. В большинстве образцов проводимость осуществляется по механизму прыжковой проводимости с переменной длиной прыжка в режиме Мотта (n = 4). В системе Ho₁₋ₓSrₓCoO₃₋δ при увеличеmги величины σ² происходит переход к прыжковой проводимости между ближайшими соседями (n = 1), а в системе Er₁₋ₓSrₓCoO₃₋δ - к режиму Эфроса-Шкловского (n = 2). В образцах Ho₁₋ₓSrₓCoO₃₋δ при повышении температуры до 190-270 К обнаружено появление спинового канала проводимости, связанное с переходом ионов кобальта в возбужденное состояние.